Effect Of Soil and foliar Fertilization Of Boron Element ON Productivity of pistachio Trees Cuitivar Nab Aljamal. (Journal of Hama University, 2022)
This research was conducted on pistachio trees of the camel tusk variety with age (30) years of cultivation. With the aim of finding out the effect of fertilization (2019-2020) in the village of Taybat Imam of Hama Governorate within two years With boron, whether sprayed on the leaves or adding it to the soil in the productivity of these trees, the following are the most important results that were reached: Fertilization with boron, whether it was added to the soil or sprayed on the leaves, contributed to the production of trees and improved the quality of their fruits compared with the control. Greater than ground fertilization in most traits. The studied experience. The highest percentage of contract and largest tree production was found in the Maameltene trees So that the percentage of the contract reached (T7-T9) while the contract percentage did not exceed (32.77) (Kg / tree), and production (56.85)% (T9)in the treatment trees. in treatment of the witness (12.66) and production% (49.43) KgThe lowest percentage of falling fruits and the lowest percentage of empty fruits reached (T5).Respectively% (7.08),% (64.20)%The highest percentage of cracked fruits and the highest fruit clearance percentage. (T7) were investigated by treatment trees Respectively% (33.02)% (43.65(%